2005
DOI: 10.1354/vp.42-3-360
|View full text |Cite
|
Sign up to set email alerts
|

Lipid-rich Carcinoma of the Mammary Gland in a Cat

Abstract: Abstract. A 1.5-year-old female, intact, clinically healthy cat presented for a subcutaneous mass of the ventral abdomen. Surgical excision and microscopic examination of the mass were performed. Histologically, this was a discrete, unencapsulated, multilobular, expansile mass, which compressed the surrounding normal mammary tissue. Lobules were composed of tubuloacinar structures formed by atypical round to polygonal cells, which contained foamy to microvacuolated cytoplasm and variably sized, intracytoplasmi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
14
1
2

Year Published

2010
2010
2020
2020

Publication Types

Select...
3
2
2

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(17 citation statements)
references
References 5 publications
0
14
1
2
Order By: Relevance
“…In the current case peritumoral neoplastic embolization and distant metastases in the right axillary lymph node, right thoracic wall, pleura, lungs, liver, spleen and kidney were seen. In contrast to our study, no metastatic lesions were identified in the feline case reported by Kamstock et al (2005).…”
Section: Resultscontrasting
confidence: 99%
See 3 more Smart Citations
“…In the current case peritumoral neoplastic embolization and distant metastases in the right axillary lymph node, right thoracic wall, pleura, lungs, liver, spleen and kidney were seen. In contrast to our study, no metastatic lesions were identified in the feline case reported by Kamstock et al (2005).…”
Section: Resultscontrasting
confidence: 99%
“…Nuclei demonstrated marked atypia, were round to angular, variably sized, predominantly euchromatic, and basophilic with occasional prominent nucleoli. Mitotic figures were infrequent (Kamstock et al, 2005). Neoplastic cells demonstrated intense and diffuse immunoreactivity for cytokeratin and lacked immunoreactivity for vimentin.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…17 Although the vacuolated cells of the present neoplasm were sometimes arranged in a tubular or cystic growth pattern, lipid-rich carcinomas in the dog and cat are also composed of tubular or tubuloacinar structures formed by lipid-rich neoplastic cells. 6,13 A recent study showed that apocrine secretion by the neoplastic luminal epithelial cells was observed in all 12 reported cases of mammary neoplasms (adenomas and/or carcinomas) in Djungarian hamsters. 8 The recurrent tumor in the present case had multifocal tubular or cystic structures lined by foamy, neutral, lipid-rich neoplastic cells suggesting apocrine secretion.…”
mentioning
confidence: 99%